Optimization of wire bond process for yield improvement with ball grid array - Foo, Chiu Peng. (2008)
The objective of this project was to improve the process yield of Ball Grid Array (BGA) packages. Preliminary analysis indicated that 42.2% of the yield losses during the wire bonding of BGA packages was due to Non-stick on Pad (NSOP). The main focus of this project was to optimise the processing parameters to enhance the adhesion between the ball bond and bond pad, so as to reduce NSOP occurrence.